2012
DOI: 10.1016/j.neuroimage.2011.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The variation of function across the human insula mirrors its patterns of structural connectivity: Evidence from in vivo probabilistic tractography

Abstract: The human insula is a functionally complex yet poorly understood region of the cortex, implicated in a wide range of cognitive, motor, emotion and somatosensory activity. To elucidate the functional role of the insula, the current study used in vivo probabilistic tractography to map the structural connectivity of seven anatomically-defined insular subregions. The connectivity patterns identified reveal two complementary insular networks connected via a dual route architecture, and provide key insights about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
176
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(198 citation statements)
references
References 72 publications
22
176
0
Order By: Relevance
“…Both display an anterior-posterior pattern evolving from agranular to granular cortices through a transitional dysgranular area and a similar pattern of connectivity with extrainsular regions, primarily governed by the cytoarchitectonic features of the connected brain regions [Cerliani et al, 2011]. In line with the above observations, a recent in vivo tractography study reported an anterior-posterior connectivity predominating over the transitional area of the human r Human Intrainsular Connectivity r r 5 r insula, particularly between the PSG and the ALG [Cloutman et al, 2011]. However, whether intrainsular functional connectivity overlaps with these structural data remained to be determined.…”
Section: Discussionsupporting
confidence: 58%
“…Both display an anterior-posterior pattern evolving from agranular to granular cortices through a transitional dysgranular area and a similar pattern of connectivity with extrainsular regions, primarily governed by the cytoarchitectonic features of the connected brain regions [Cerliani et al, 2011]. In line with the above observations, a recent in vivo tractography study reported an anterior-posterior connectivity predominating over the transitional area of the human r Human Intrainsular Connectivity r r 5 r insula, particularly between the PSG and the ALG [Cloutman et al, 2011]. However, whether intrainsular functional connectivity overlaps with these structural data remained to be determined.…”
Section: Discussionsupporting
confidence: 58%
“…The middle insular cortex has connections with frontal (superior, inferior, and precentral), parietal (postcentral and supramarginal), and temporal (inferior and superior) gyri. Finally, the posterior insular cortex has connections with frontal (superior, inferior, and precentral), parietal (postcentral), and temporal (inferior and superior) gyri and with the putamen (Cerliani et al, 2012;Cloutman et al, 2012;Jakab et al, 2012). These results are in accordance with tract-tracing studies but some connections in primates were not found in humans.…”
Section: Structural Connectivitysupporting
confidence: 84%
“…Brownsett et al, (2014)) and establishing a more exact role for the multiple attentional networks engaged during speech comprehension (Corbetta & Shulman, 2011;Dosenbach, Fair, Cohen, Schlaggar, & Petersen, 2008;Evans et al, 2016;Petersen & Posner, 2012). Further advances are also likely to come from approaches that constrain the definition of functional networks dependent on the underlying anatomy -studies using diffusion weighted imaging have identified patterns of structural connectivity supportive of prior evidence for functional segregation within regions such as the insula and rostral temporal lobe Cloutman, Binney, Drakesmith, Parker, & Lambon Ralph, 2012), and described subdivisions of the dorsal route for language processing (Cloutman, Binney, Morris, Parker, & Lambon Ralph, 2013). RSA may again prove a useful approach to synthesise this kind of structural and functional data (Lima, Lavan et al, 2015).…”
Section: Future Directionsmentioning
confidence: 99%